Combination Therapy of Amniotic Membrane Transplantation with Conjunctival Peritomy and Autologous Serum for Mooren's Ulcer: A Case Report: Poster Presentation - Case Report - Resident - AUFAA SHAFIRA WIDOWATI; Suhardjo Pawiroranu; Reny Setyowati (Majalah Oftalmologi Indonesia, 2023)
Introduction : A case report of a patient with Mooren’s ulcer who received partial amniotic membrane transplantation and autologous serum eye drops. Case Illustration : A 44-year-old male patient presented with chief complaint of blurred vision, pain in left eye, and history of eye trauma 6 months prior. Empirical topical antibiotics didn’t improve his condition. VA of left eye was hand movement with good colour/light perception. We diagnosed the patient with marginal ulcer. Partial amniotic membrane transplantation with conjunctival peritomy was planned for this patient along with fortified antibiotic eye drops. Autologous serum eye drops were started at 2 weeks post-surgery. 2 months after surgery, his condition has significantly improved with visual acuity of 6/12 (Snellen), healed corneal defect, and subjective relief of symptoms. Discussion : Mooren’s ulcer is a severe ulcerative inflammation of the cornea with unclear exact pathogenesis. Many therapies of Mooren’s ulcer are recommended in literatures, including surgical and non- surgical treatment. It was reported that amniotic membrane transplantation and conjunctival peritomy may be chosen as alternative surgical procedure for Mooren’s ulcer, as peritomy displaces the source of inflammation away from the cornea and amniotic membrane helps in corneal reepithelialization. Autologous serum is considered as an effective adjuvant therapy for ocular surface diseases such as dry eye disease, cicatricial pemphigoid, Steven-Johnson syndrome, and Mooren’s ulcer—thus the decision to include the therapy in our regiment. Conclusion : The combination of amniotic membrane transplantation, conjunctival peritomy, and autologous serum may help in the overall improvement of patients with Mooren’s ulcer.